simplify your first derivative before going further
notice you can divide each term by 1/3 to get
x^(-2/3) + y^(-2/3) dy/dx = 0
dy/dx = -x^(-2/3) / y^(-2/3)
= - y^(2/3)/x^(2/3)
= - (y/x)^(2/3)
d^2y/dx^2 = (-2/3) (y/x)^(-1/3) [( xdy/x - y)/x^2)
replace the dy/dx in the square bracket by (y/x)^2/3) and see what you get.
Still messy but a small improvement.
12th AP Calculus - use implicit differentiation to find dy/dx and then d^2y/dx^2...
calculus - find dy/dx implicit differentiation x^2y+y^2x=0 at x=-2, x=2
Calculus - Find dy/dx by implicit differentiation. sqrt(3 x+y)=2+x^2y^2?
Calculus - Use implicit differentiation to find dy/dx. e^4x = sin(x+2y). This is...
calculus help - implicit differentation 1.y^3=4(x^2+y^2) 2.y^2-3x+2y=0 help ...
Math - Find dx/dy by implicit differentiation x^2y+y^2x P.S: It's calculus
Calculus - Find dy/dx by implicit differentiation for the following 2x^2y+3y=-1
Calculus 1 Implicit differentiation - Help please help me understand what i am ...
Math/Calculus. - Suppose (x^2)*(e^(-2y))= ln(xy) Find dy/dx by implicit ...
12th calculus - find dy/dx by implicit differentation and evaluate the ...